Studi Kecernaan dan Konsumsi Pakan pada Kambing Peranak Etawah Jantan Muda yang diberi Pakan Hijauan Mengandung Tannin Kondensasi - Willy Rochel; Afzalani Afzalani; R. A. Muthalib; Raguati Raguati; Fachroerrozi Hoesni (Universitas Batanghari Jambi, 2023)
This study aims to determine the effectiveness of using various levels of forage sengon leaves (Albizia falcataria) as a source of condensed tannin on dry matter intake (DMI), organic matter intake (OMI), digestible dry matter intake (DDMI), digestible organic matter intake (DOMI), dry matter digestibility (DMD), and organic matter digestibility (OMD). This study used sixteen young male ettawa cross-breed goats aged 8â€“12 months with an average body weight range of 19Â±1.8 kg. The study was arranged in a randomized block design (RBD) with four treatments and four bodyweight groups as replicates. Diet treatments consisted of R0: 60% Brachiaria mutica (BM) + 0% A. falcataria (AF) Leaf + 40% Concentrate (CON), R1: 50% BM + 10% AF Leaf + 40% Concentrate, R2: 40% BM + 20% AF Leaf + 40% CON, and R3: 30% BM + 30% AF Leaf + 40% CON. The results showed that the use of sengon leaves as a source of condensed tannin in diets significantly (P 0.05) reduced DMI, OMI, DDMI, and DOMI but did not significantly (P > 0.05) affect DMD and OMD values. This study concluded that AF leaf as a forage source containing condensed tannin made up as much as 30%, or equivalently, 50%, of the forage in the diet of young male ettawa cross-breed goats without having any effect on diet intake or digestibility.